(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
In this paper, we report a bending fatigue testing apparatus which can test the bending fatigue resistance of single Kevlar 49 fiber by setting the pretension and bending angle. The cyclic tension and the (number of cyclic bending of fiber) were recorded by this apparatus. The cyclic tension curve showed that the tension changes in periods during the bending fatigue process. The cyclic tension was theoretically analyzed and found that the bending angle had significant effect on the cyclic tension. The cyclic bending number N of Kevlar 49 fiber was plotted as a function of pretension S using S-N curves, which shows that the bending angle and pretension have a significant effect on the fatigue lifetime of a fiber. The bending fatigue morphologies of Kevlar 49 fiber explained the bending failure mechanism of the Kevlar 49 fibers.